X4-ROV: the open source underwater vehicle - Zainah, Md. Zain; Khairil Ashraff, Ab Rahim (Springer Singapore, 2018)
The biggest bottleneck of currently available Remotely Operated Ve-hicles (ROVs) is the cost of the systems. Therefore, to reduce operational costs and system complexity, the development of micro or handheld inspection ROVs has been increasing lately. An open-source underwater vehicle startup has con-tributed to the community by producing cheap ROVs, encouraging users to de-velop their own underwater vehicle. In this project, a low-cost ROV prototype, called X4-ROV using open-source OpenROV computer hardware and software is developed. This new design includes hardware, firmware, software and con-trol architectures.